2006
DOI: 10.1385/ncc:4:3:199
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Left Ventricular Regional Wall Motion Abnormalities After Subarachnoid Hemorrhage

Abstract: RWMA were frequent after SAH. High-grade SAH, an elevation in cTi levels, a history of prior stimulant drug use, and tachycardia are independent predictors of RWMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 29 publications
4
77
0
1
Order By: Relevance
“…This observation is consistent with the previous finding that myocardial damage was associated with more severe SAH grades. 10,11,29) Moreover, we found that RWMA predicts poor outcome after SAH, suggesting RWMA in SAH reflects adverse intracranial factors. In the present study, global LV dysfunction (LVEF < 50%) did not predict poor outcome after SAH.…”
Section: Dysfunction In Sahmentioning
confidence: 60%
See 1 more Smart Citation
“…This observation is consistent with the previous finding that myocardial damage was associated with more severe SAH grades. 10,11,29) Moreover, we found that RWMA predicts poor outcome after SAH, suggesting RWMA in SAH reflects adverse intracranial factors. In the present study, global LV dysfunction (LVEF < 50%) did not predict poor outcome after SAH.…”
Section: Dysfunction In Sahmentioning
confidence: 60%
“…4,12,13,28,29) We also have shown that the most frequently abnormal LV segments were the middle ventricular portions of the anterolateral, posterolateral, and inferior walls and basal portion of the anterior wall. This pattern did not correlate with coronary artery distributions, suggesting SAH-associated heart damage is a form of neurocardiogenic injury.…”
Section: Dysfunction In Sahmentioning
confidence: 73%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] WMA occurs in patients with SAH with a reported incidence of 8% to 27%. 5,7,8 It has been hypothesized that massive release of catecholamine into the systemic circulation after SAH results in the nonischemic usually reversible myocardial injury.…”
mentioning
confidence: 99%
“…5,7,8 It has been hypothesized that massive release of catecholamine into the systemic circulation after SAH results in the nonischemic usually reversible myocardial injury. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] In the cardiology literature, the possible role of estrogen in the pathogenesis of WMA has recently been suggested in patients with takotsubo (stress) cardiomyopathy (TCM). 16 -18 This hypothesis is based on the clinical observation that a majority of patients with TCM are postmenopausal women, whereas only a few young women are diagnosed with TCM.…”
mentioning
confidence: 99%
“…Presentation includes transient lactic acidosis, cardiogenic shock, pulmonary edema, widespread T wave inversions, and reversible wall motion abnormalities [63]. One prospective study revealed a 18% (35% in Grade III-V) prevalence of wall motion abnormalities on echocardiogram in patients with aneurysmal SAH [64]. Takotsubo cardiac myopathy, also known as apical ballooning syndrome, is a subset of stunned myocardial injury seen most commonly in postmenopausal women and is associated with pulmonary edema and prolonged mechanical ventilation [65].…”
Section: Cardiac Complicationsmentioning
confidence: 99%